The Application of Bioedutainment Strategy Using Uno Cards on the Studentsâ Learning Result in Invertebrate Material at Sma Institut Indonesia - Khomsah, Irma; Heri B, F Putut Martin; Irsadi, Andin (Journal of Biology Education, 2018)
This study aims to examine the effect of applying uno-assisted bioedutainment strategy on studentsâ learning outcomes in invertebrate material. This study uses a non-equivalent control group design. The population of this study is the students of class X SMA Institut Indonesia Semarang. X.4 and X.5 were selected as samples using purposive sampling technique. The result of the study showed that there were significant differences in the data of the second post tested class. T test analysis of post test students shows t count> t table. The conclusion of this study is that the learning using uno cards in invertebrate material has a positive effect on the studentsâ learning outcomes.